Psychological preparation for paralympic athletes: a preliminary study - Blumenstein, B.; Orbach, I. (Adapted Physical Activity Quarterly, 2015)
Since the first Paralympics in 1960 there has been an increase in social and scientific interest in Paralympic athletes` personality, their preparation, and their sport results. During the last 20 yr, researchers and practitioners have been focused on psychological-skills programs for athletes with disabilities. The purpose of this article was to describe a psychological-preparation program for Israeli Paralympic athletes. Two subprograms, the learning-modification-application approach and the Simulation Training Exercise Program, were adapted to athletes` disability and sport demands. Two case studies, from table tennis and sailing (Sonar 3-person keelboat), are described to demonstrate how systematic sport psychology preparation can be effectively integrated into the training process of Paralympic athletes. Some recommendations for Paralympic athletes are presented.